High-purity aluminum nitride ceramic and preparation method thereof

Through the use of modified dispersants and binders and isostatic and hot press sintering technologies, the problem of high-purity aluminum nitride ceramics not being dense under normal pressure is solved, and the high density and excellent mechanical properties of the ceramics are achieved.

CN119841648AInactive Publication Date: 2025-04-18FUJIAN HUAQING ELECTRONICS MATERIAL TECH

Patent Information

Application Number
CN202510341951.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing high-purity aluminum nitride ceramics are not densely sintered under normal pressure, requiring higher sintering temperature and insulation time, and the body density distribution is unevenly distributed during the hot pressing sintering process, affecting the density and performance of the ceramics.

Method used

High-purity aluminum nitride ceramics are prepared through granulation, glue discharge sintering, isostatic molding, hot press sintering and cooling grinding. The green body density is increased by using modified dispersants and binders, and the sintering temperature and time are reduced through isostatic and hot press sintering techniques to improve the density of the ceramics.

Benefits of technology

The good mechanical strength and density of high-purity aluminum nitride ceramics are achieved, the sintering temperature and time are reduced, and the body density is uniformly distributed, the pore generation is reduced, and the bonding density between grains is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic materials, in particular to high-purity aluminum nitride ceramic and a preparation method thereof.The preparation method of the high-purity aluminum nitride ceramic comprises the following steps that S1, granulation is conducted, specifically, aluminum nitride, a dispersing agent and modified polyvinyl butyral are mixed and granulated; s2, dumping and sintering: performing thermal degreasing in a dumping furnace, setting the heating rate to be 0.5-1.5 DEG C / min, setting the degreasing temperature to be 500-600 DEG C, and keeping the temperature for 2-4 hours; s3, compression molding: pressing into a green body by using an isostatic press, and controlling the molding pressure to be 80-100Mpa; s4, hot pressed sintering: smearing the protective liquid on the surface of the green body, and sintering in a heating and pressurizing manner; and S5, cooling and grinding are conducted, specifically, the sintered body is cooled to the normal temperature and ground to be flat. According to the preparation method of the high-purity aluminum nitride ceramic, the obtained ceramic chip has good mechanical strength and compactness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic materials, and in particular to a high-purity aluminum nitride ceramic and a preparation method thereof. Background Art

[0002] As global wafer fabs continue to expand production, the global semiconductor equipment and parts market continues to grow rapidly. Among them, advanced ceramics account for an increasingly higher proportion of the value of semiconductor equipment parts and components, and are core key components with extremely high technical barriers and processing difficulties.

[0003] Semiconductor equipment consists of equipment inside and outside the chamber. Most ceramic parts are used in chambers closer to the wafers. They are key parts and require high purity. Fewer impurities can reduce the risk of wafer contamination. The main application needs are in equipment such as etching, thin film deposition, photolithography, and oxidation diffusion. Aluminum nitride ceramics are core parts for semiconductor equipment prepared after precision processing, and have excellent properties such as high thermal conductivity, high strength, corrosion resistance, high insulation, and low thermal expansion.

[0004] At present, there are relatively few developments of high-purity aluminum nitride ceramics above 99% in China. Most of them have added sintering aids, resulting in the purity of aluminum nitride ceramics being only about 95%. However, without adding sintering aids, aluminum nitride ceramics are not dense when sintered under normal pressure, and require higher sintering temperatures and insulation time to achieve the effect of increasing the density of aluminum nitride ceramics. With the development of hot pressing sintering, the density of ceramics has been improved by using hot pressing sintering technology to sinter aluminum nitride, and the sintering temperature is relatively low, but it is still not ideal. There are also methods to increase the density of the green body by dry pressing or hot pressing preforming, but dry pressing is unevenly stressed in all directions, resulting in uneven density distribution of the green body, and hot pressing preforming is sometimes subject to the limitation of pressurization pressure, resulting in poor green body preforming effect, which ultimately affects the density and performance of aluminum nitride ceramics after hot pressing sintering. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a high-purity aluminum nitride ceramic and a preparation method thereof, and the obtained ceramic sheet has good mechanical strength and density.

[0006] In order to achieve the above object, the present invention provides the following technical solutions: A method for preparing high-purity aluminum nitride ceramics comprises the following steps: S1: Granulation: mixing aluminum nitride, a dispersant and modified polyvinyl butyral to form granules; S2: Debinding sintering: thermal debinding is performed in a debinding furnace, the heating rate is set at 0.5-1.5℃ / min, the debinding temperature is set at 500-600℃, and the temperature is kept for 2-4h; S3: Compression molding: using an isostatic press to press into a green body, the molding pressure is controlled at 80-100Mpa; S4: hot pressing sintering: the protective liquid is applied to the surface of the green body, and sintering is performed by increasing temperature and pressure; S5: Cooling and grinding: The sintered body is cooled to room temperature and ground.

[0007] Preferably, in step S1, the weight ratio of aluminum nitride, dispersant and modified polyvinyl butyral is 96:1:3.

[0008] Preferably, the dispersant in step S1 is modified carboxymethyl cellulose.

[0009] Preferably, the preparation method of the modified carboxymethyl cellulose is as follows: didecyl dimethyl ammonium chloride, chitosan, carboxymethyl cellulose and a 50% by volume ethanol solution are mixed, stirred at 30-40° C. for 4-6 hours, and vacuum dried to obtain the modified carboxymethyl cellulose.

[0010] Preferably, the weight ratio of didecyldimethylammonium chloride, chitosan, carboxymethyl cellulose and ethanol solution is 1:1:2:4.

[0011] Preferably, the preparation method of the modified polyvinyl butyral is specifically as follows: polyvinyl butyral, polyvinyl alcohol, an ethanol solution with a volume fraction of 50% and graphene are mixed, stirred for 12-24 hours, and vacuum dried to obtain the modified polyvinyl butyral.

[0012] Preferably, the weight ratio of the polyvinyl butyral, polyvinyl alcohol, 50% by volume ethanol solution and graphene is 4:1:5:1.

[0013] Preferably, in step S4, applying the protective liquid to the surface of the blank specifically comprises: preparing a solution of boron nitride powder and anhydrous ethanol in a ratio of 1:1, spraying it evenly on the formed blank, wrapping it with graphite paper, and then spraying the boron nitride solution on the outer surface of the graphite paper.

[0014] Preferably, the specific process of the heating and pressurizing method in step S4 is: in a graphite mold, nitrogen is filled for sintering, and before heating, it is first evacuated to below 5Pa, and then 105Kpa nitrogen is filled, and the temperature is increased to 1200°C at a heating rate of 10°C / min, and then slowly increased to 1800°C at 1°C / min, and kept warm for 3h. When the temperature rises to 1200°C, pressurize at 0.04Mpa / min, and enter the preservation pressure state at the same time when the temperature reaches 1800°C, and the holding pressure is 24Mpa.

[0015] A high-purity aluminum nitride ceramic is prepared by the above preparation method.

[0016] The present invention has both flexibility and high-strength bonding properties by modifying the dispersant and the binder, and makes the aluminum nitride powder particles contact more closely by adsorbing and bonding the aluminum nitride particles, thereby increasing the green body density and promoting the transfer of substances. After sintering, the generation of pores is reduced, so that the bonding between the grains is better and the density is higher. In addition, through isostatic pressing + protective liquid coating and temperature increase and pressure, the green body has more complete grain growth as the sintering temperature increases, the pores between the grains are further reduced, and the bonding is more closely. In addition, As the sintering pressure increases, the grains are more closely combined, which is conducive to densification sintering. Finally, by extending the holding time, the lattice is further purified, the grains are promoted to grow and the porosity is significantly reduced. The green body is first isostatically pressed and then hot-pressed and sintered. Due to the uniform force in all directions, the density distribution of the green body is uniform, and the green body has high strength, which is conducive to the subsequent green body transfer and reduces sintering defects. Compared with normal pressure sintering, hot pressing sintering can effectively reduce the sintering temperature and time, and obtain aluminum nitride ceramics with good density and excellent strength. DETAILED DESCRIPTION

[0017] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. In addition, it is specifically stated that the raw materials and equipment of the present invention can be obtained from commercial sources, and no longer listed one by one. Among them, the raw materials of the present invention can be obtained from commercial sources and are well known to those skilled in the art. Example 1

[0018] A method for preparing high-purity aluminum nitride ceramics comprises the following steps: S1: Granulation: Aluminum nitride, modified carboxymethyl cellulose and modified polyvinyl butyral are mixed and granulated in a weight ratio of 96:1:3; The preparation method of modified carboxymethyl cellulose is as follows: didecyl dimethyl ammonium chloride, chitosan, carboxymethyl cellulose and 50% ethanol solution by volume are mixed in a weight ratio of 1:1:2:4, stirred at 30°C for 4h, and vacuum dried to obtain modified carboxymethyl cellulose; The preparation method of the modified polyvinyl butyral is specifically as follows: polyvinyl butyral, polyvinyl alcohol, an ethanol solution with a volume fraction of 50%, and graphene are mixed in a weight ratio of 4:1:5:1, stirred for 12 hours, and vacuum dried to obtain the modified polyvinyl butyral; S2: Debinding sintering: thermal debinding is performed in a debinding furnace, the heating rate is set at 0.5°C / min, the debinding temperature is set at 500°C, and the temperature is kept for 2 hours; S3: Compression molding: using an isostatic press to press into a green body, the molding pressure is controlled at 80Mpa; S4: hot pressing sintering: prepare a solution with boron nitride powder and anhydrous ethanol in a ratio of 1:1, spray it evenly on the formed body, wrap it with graphite paper, and then spray the boron nitride solution on the outer surface of the graphite paper. Sinter it in a graphite mold with nitrogen. Before heating, evacuate to below 5Pa, then fill with 105Kpa nitrogen, heat it to 1200℃ at a heating rate of 10℃ / min, and then slowly heat it to 1800℃ at 1℃ / min, and keep it warm for 3h. When the temperature rises to 1200℃, pressurize it at 0.04Mpa / min, and enter the storage pressure state at the same time when the temperature reaches 1800℃, and sinter it at a holding pressure of 24Mpa; S5: Cooling and grinding: The sintered body is cooled to room temperature and ground.

[0019] A high-purity aluminum nitride ceramic is prepared by the above preparation method. Example 2

[0020] A method for preparing high-purity aluminum nitride ceramics comprises the following steps: S1: Granulation: Aluminum nitride, modified carboxymethyl cellulose and modified polyvinyl butyral are mixed and granulated in a weight ratio of 96:1:3; The preparation method of modified carboxymethyl cellulose is as follows: didecyl dimethyl ammonium chloride, chitosan, carboxymethyl cellulose and 50% ethanol solution by volume are mixed in a weight ratio of 1:1:2:4, stirred at 40°C for 6 hours, and vacuum dried to obtain modified carboxymethyl cellulose; The preparation method of the modified polyvinyl butyral is specifically as follows: polyvinyl butyral, polyvinyl alcohol, an ethanol solution with a volume fraction of 50%, and graphene are mixed in a weight ratio of 4:1:5:1, stirred for 24 hours, and vacuum dried to obtain the modified polyvinyl butyral; S2: Debinding sintering: thermal debinding is performed in a debinding furnace, the heating rate is set at 1.5°C / min, the debinding temperature is set at 600°C, and the temperature is kept for 4 hours; S3: Compression molding: using an isostatic press to press into a green body, the molding pressure is controlled at 100Mpa; S4: hot pressing sintering: prepare a solution with boron nitride powder and anhydrous ethanol in a ratio of 1:1, spray it evenly on the formed body, wrap it with graphite paper, and then spray the boron nitride solution on the outer surface of the graphite paper. Sinter it in a graphite mold with nitrogen. Before heating, evacuate to below 5Pa, then fill with 105Kpa nitrogen, heat it to 1200℃ at a heating rate of 10℃ / min, and then slowly heat it to 1800℃ at 1℃ / min, and keep it warm for 3h. When the temperature rises to 1200℃, pressurize it at 0.04Mpa / min, and enter the storage pressure state at the same time when the temperature reaches 1800℃, and sinter it at a holding pressure of 24Mpa; S5: Cooling and grinding: The sintered body is cooled to room temperature and ground.

[0021] A high-purity aluminum nitride ceramic is prepared by the above preparation method. Example 3

[0022] A method for preparing high-purity aluminum nitride ceramics comprises the following steps: S1: Granulation: Aluminum nitride, modified carboxymethyl cellulose and modified polyvinyl butyral are mixed and granulated in a weight ratio of 96:1:3; The preparation method of modified carboxymethyl cellulose is as follows: didecyl dimethyl ammonium chloride, chitosan, carboxymethyl cellulose and 50% ethanol solution by volume are mixed in a weight ratio of 1:1:2:4, stirred at 35°C for 5h, and vacuum dried to obtain modified carboxymethyl cellulose; The preparation method of the modified polyvinyl butyral is specifically as follows: polyvinyl butyral, polyvinyl alcohol, an ethanol solution with a volume fraction of 50%, and graphene are mixed in a weight ratio of 4:1:5:1, stirred for 18 hours, and vacuum dried to obtain the modified polyvinyl butyral; S2: Debinding sintering: thermal debinding is performed in a debinding furnace, the heating rate is set at 1.0°C / min, the debinding temperature is set at 550°C, and the temperature is kept for 3 hours; S3: Compression molding: using an isostatic press to press into a green body, the molding pressure is controlled at 90Mpa; S4: hot pressing sintering: prepare a solution with boron nitride powder and anhydrous ethanol in a ratio of 1:1, spray it evenly on the formed body, wrap it with graphite paper, and then spray the boron nitride solution on the outer surface of the graphite paper. Sinter it in a graphite mold with nitrogen. Before heating, evacuate to below 5Pa, then fill with 105Kpa nitrogen, heat it to 1200℃ at a heating rate of 10℃ / min, and then slowly heat it to 1800℃ at 1℃ / min, and keep it warm for 3h. When the temperature rises to 1200℃, pressurize it at 0.04Mpa / min, and enter the storage pressure state at the same time when the temperature reaches 1800℃, and sinter it at a holding pressure of 24Mpa; S5: Cooling and grinding: The sintered body is cooled to room temperature and ground.

[0023] A high-purity aluminum nitride ceramic is prepared by the above preparation method. Comparative Example 1:

[0024] The preparation method of Comparative Example 1 is basically the same as that of Example 1, except that carboxymethyl cellulose and polyvinyl butyral are directly used, specifically: A method for preparing high-purity aluminum nitride ceramics comprises the following steps: S1: Granulation: Aluminum nitride, carboxymethyl cellulose and polyvinyl butyral are mixed and granulated in a weight ratio of 96:1:3; S2: Debinding sintering: thermal debinding is performed in a debinding furnace, the heating rate is set at 0.5°C / min, the debinding temperature is set at 500°C, and the temperature is kept for 2 hours; S3: Compression molding: using an isostatic press to press into a green body, the molding pressure is controlled at 80Mpa; S4: hot pressing sintering: prepare a solution with boron nitride powder and anhydrous ethanol in a ratio of 1:1, spray it evenly on the formed body, wrap it with graphite paper, and then spray the boron nitride solution on the outer surface of the graphite paper. Sinter it in a graphite mold with nitrogen. Before heating, evacuate to below 5Pa, then fill with 105Kpa nitrogen, heat it to 1200℃ at a heating rate of 10℃ / min, and then slowly heat it to 1800℃ at 1℃ / min, and keep it warm for 3h. When the temperature rises to 1200℃, pressurize it at 0.04Mpa / min, and enter the storage pressure state at the same time when the temperature reaches 1800℃, and sinter it at a holding pressure of 24Mpa; S5: Cooling and grinding: The sintered body is cooled to room temperature and ground.

[0025] A high-purity aluminum nitride ceramic is prepared by the above preparation method. Comparative Example 2:

[0026] The preparation method of Comparative Example 2 is basically the same as that of Example 1, except that carboxymethyl cellulose and polyvinyl butyral are directly used, and the green body is directly sintered without using a protective liquid, specifically: A method for preparing high-purity aluminum nitride ceramics comprises the following steps: S1: Granulation: Aluminum nitride, carboxymethyl cellulose and polyvinyl butyral are mixed and granulated in a weight ratio of 96:1:3; S2: Debinding sintering: thermal debinding is performed in a debinding furnace, the heating rate is set at 0.5°C / min, the debinding temperature is set at 500°C, and the temperature is kept for 2 hours; S3: Compression molding: using an isostatic press to press into a green body, the molding pressure is controlled at 80Mpa; S4: Hot pressing sintering: first evacuate to below 5Pa, then fill with 105Kpa nitrogen, enter the storage pressure state at 1800℃, and sinter at a holding pressure of 24Mpa; S5: Cooling and grinding: The sintered body is cooled to room temperature and ground.

[0027] A high-purity aluminum nitride ceramic is prepared by the above preparation method.

[0028] The following tests were conducted on Examples 1-3, the commercially available ceramic sheets produced by Yixing Borilient Precision Ceramics Co., Ltd., and Comparative Examples 1-2.

[0029] Performance Test: Density test: Tested in accordance with QB / T1642-2012.

[0030] Mechanical strength test: Tested in accordance with GB / T 4740-1999.

[0031] Thermal conductivity: LFA467 thermal conductivity tester (10mm*2.0mm specification sample) is used.

[0032] The density, strength and thermal conductivity were tested by taking 100 ceramic pieces and taking the average value of the test results.

[0033] Table 1: Test data of examples 1-3, commercially available ceramic sheets and comparative examples 1-2

[0034] It can be seen from the above table that the density and strength of the ceramic sheets prepared in Examples 1-3 are relatively good.

[0035] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing high-purity aluminum nitride ceramics, characterized in that: The following steps are involved: S1: Granulation: mixing aluminum nitride, a dispersant and modified polyvinyl butyral to form granules; S2: Debinding sintering: thermal debinding is performed in a debinding furnace, the heating rate is set at 0.5-1.5℃ / min, the debinding temperature is set at 500-600℃, and the temperature is kept for 2-4h; S3: Compression molding: using an isostatic press to press into a green body, the molding pressure is controlled at 80-100Mpa; S4: hot pressing sintering: the protective liquid is applied to the surface of the green body, and sintering is performed by increasing temperature and pressure; S5: Cooling and grinding: cooling the sintered body to room temperature and grinding it; In step S1, the dispersant is modified carboxymethyl cellulose; the preparation method of the modified carboxymethyl cellulose is specifically as follows: didecyl dimethyl ammonium chloride, chitosan, carboxymethyl cellulose and a 50% by volume ethanol solution are mixed, stirred at 30-40° C. for 4-6 hours, and vacuum dried to obtain the modified carboxymethyl cellulose; The preparation method of the modified polyvinyl butyral is specifically as follows: polyvinyl butyral, polyvinyl alcohol, an ethanol solution with a volume fraction of 50% and graphene are mixed, stirred for 12-24 hours, and vacuum dried to obtain the modified polyvinyl butyral.

2. The method for preparing high-purity aluminum nitride ceramics according to claim 1, characterized in that: In the step S1, the weight ratio of aluminum nitride, dispersant and modified polyvinyl butyral is 96:1:

3.

3. The method for preparing high-purity aluminum nitride ceramics according to claim 1, characterized in that: The weight ratio of the didecyl dimethyl ammonium chloride, chitosan, carboxymethyl cellulose and ethanol solution is 1:1:2:

4.

4. The method for preparing high-purity aluminum nitride ceramics according to claim 1, characterized in that: The weight ratio of the polyvinyl butyral, polyvinyl alcohol, 50% ethanol solution by volume and graphene is 4:1:5:

1.

5. The method for preparing high-purity aluminum nitride ceramics according to claim 1, characterized in that: In step S4, applying the protective liquid to the surface of the blank specifically includes: preparing a solution of boron nitride powder and anhydrous ethanol in a ratio of 1:1, spraying it evenly on the formed blank, wrapping it with graphite paper, and then spraying the boron nitride solution on the outer surface of the graphite paper.

6. The method for preparing high-purity aluminum nitride ceramics according to claim 1, characterized in that: The specific process of the heating and pressurizing method in step S4 is as follows: in a graphite mold, nitrogen is filled for sintering. Before heating, the temperature is first evacuated to below 5Pa, and then 105Kpa nitrogen is filled in. The temperature is raised to 1200°C at a heating rate of 10°C / min, and then slowly raised to 1800°C at a heating rate of 1°C / min, and kept warm for 3 hours. When the temperature rises to 1200°C, pressurize at 0.04Mpa / min, and enter the storage pressure state at the same time when the temperature reaches 1800°C, with a holding pressure of 24Mpa.

7. A high-purity aluminum nitride ceramic, characterized in that: The product is prepared by the preparation method described in claim 1.

Citation Information

Patent Citations

  • High thermal conductive aluminum nitride ceramic heat dissipation substrate and preparation method thereof

    CN103204682A

  • Improved grouting method for preparing special ceramic

    CN104446506A

  • High-performance aluminum nitride ceramic material and preparation method thereof

    CN116332653A

  • High-resistivity stable silicon nitride composite ceramic and preparation method thereof

    CN118125832A

  • High-strength nano aluminum oxide ceramic product and preparation process thereof

    CN119390466A

Cited By

  • Aluminum nitride precision ceramic for semiconductor equipment and preparation method of aluminum nitride precision ceramic

    CN122127167A

  • Aluminum nitride precision ceramic for semiconductor devices and method for manufacturing the same

    CN122127167B